The Legal Politics of Immigration: Restrictions on Foreign Citizens in Indonesia During the COVID-19 Pandemic - Rokan, Mustika Putra (LOCUS MEDIA PUBLISHING, 2023)
The COVID-19 pandemic, which began in Wuhan, China, in late 2019, has had global repercussions, including in Indonesia, particularly in the immigration sector. The policy of Large-Scale Social Restrictions (PSBB), deemed ineffective, prompted the Indonesian Government to introduce the Enforcement of Restrictions on Community Activities (PPKM) as an alternative in combating the spread of the virus. This article explores the legal politics of immigration during the emergency PPKM period of the COVID-19 pandemic in Indonesia using a normative juridical approach and literature research. Although PPKM is not explicitly regulated, it poses legal-political challenges and requires adaptation in the immigration legal system. The article also discusses the development of immigration law substance from Law No. 9/1992 to Law No. 6/2011, as well as the political-legal implications regarding the restriction of foreigners in Indonesia during PPKM. The need for legal consistency and policy adjustment in responding to pandemic challenges, as well as legal-political options that the government can take to strengthen the legal basis of PPKM and respond to changes in the immigration system, is also highlighted. Some recommended steps include changes to the Law, issuing Government Regulation in Lieu of Law (Perpu), and enhancing the role of Regional Governments in regulating PPKM in accordance with their authority.